Wake up to realities of river basin closure - Falkenmark, M.; David, S. (2008)
As societies develop, river basin water resources are increasingly controlled, diverted and consumed for agricultural, domestic and industrial purposes, hence reducing the ability to meet the growing demands from various sectors and interests. Basins are closed when additional water commitments for domestic, industrial, agricultural or environmental uses cannot be met during all or part of a year. Basin closure is already prevalent in the world today, with 1.4 billion people living in areas that have to deal with the situation. Societies may adapt to this in various ways, with reallocation of water, demand management or interbasin transfers as the primary means of dealing with the problem. However, 'quick-fix' measures such as further groundwater or surface water exploitation or ill-planned water appropriation that unfairly reallocates water from one user are common. Symptoms of poorly managed closed basins include groundwater overdraft, limited or no environmental flows, pollution and inequitable allocation of water. Thus, a pertinent question is whether there will be a hard or soft landing in closed basins?will the resource base fail to meet basic requirements causing undue hardship, or can societies adapt to achieving a soft landing. Surprisingly, limited attention has been given today to this urgent water situation.